Periodontal disease and uncommon microorganisms - Centeno Dávila , María del Cisne (2025)
Periodontal disease is characterized by the presence of complex subgingival microbial communities, encompassing up to 500 bacterial species, with Socransky’s red complex being particularly notable. However, recent systematic reviews have identified the critical role of other microorganisms in biofilm formation and dental surface colonization, including Staphylococcus aureus, Enterococcus faecalis, Helicobacter pylori, and Candida albicans, which may also act as significant pathogens within the periodontal context. This study aimed to analyze the presence of lesser-known microorganisms that could play a crucial role in periodontal disease. A descriptive documentary research approach was employed through a narrative bibliographic review, involving searches for scientific articles in databases such as Google Scholar, PubMed, SciELO, and Scopus. Thirty-four articles meeting the established inclusion criteria were selected. The presence of microorganisms including Staphylococcus aureus, Enterococcus faecalis, Helicobacter pylori, and Candida albicans was demonstrated, with their virulence and pathogenesis factors linked to periodontal disease. These were classified as opportunistic periodontopathogens; however, it was not possible to demonstrate that they are precursors of periodontal disease